2021
DOI: 10.3389/fmats.2021.733109
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Nanomechanical Characterization of Thermoplastic Biocomposites Based on Chemically Treated Lignocellulosic Biomass for Surface Engineering Applications

Abstract: Diverse applications of polymeric materials have prompted development of eco-friendly, efficient, and economical materials. These characteristics can be obtained by incorporating appropriate fillers in the polymeric matrix. The objective of this work is to investigate impact of aqueous glycerol (Gly) treated rice husk (RH) on surface mechanical properties of produced biocomposites. RH was treated with aqueous Gly (75 wt%) and compounded with low density polyethylene (LDPE) at different loadings (10, 20, and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Subsequently, the indenter began to unload. The absence of overlap between the loading and unloading curves shown in Figure 5 suggests that the developed membranes demonstrated both elastic behavior and distinct plastic characteristics [ 23 ]. The loading and unloading curves appeared continuous and stable for all developed membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the indenter began to unload. The absence of overlap between the loading and unloading curves shown in Figure 5 suggests that the developed membranes demonstrated both elastic behavior and distinct plastic characteristics [ 23 ]. The loading and unloading curves appeared continuous and stable for all developed membranes.…”
Section: Resultsmentioning
confidence: 99%
“…It could also be concluded that the decreasing impact strength of the composites indicated the accumulation of filler particles in the polymer. As a result, weak interfacial bonding between reinforcing and substrate materials may happen, leading to poor mechanical properties of the resultant composites [25].…”
Section: Impact Strength Analysismentioning
confidence: 99%
“…The outer surface was hardened compared to the inner region [24]. This could have occurred because of the environmental impact on the top surface of the composites, generating hardening effects [25]. Due to the sheets' rough and uneven top surface, a wide range of hardness and elastic modulus was found.…”
Section: Hardness Elastic Modulus Analysismentioning
confidence: 99%